Serviços farmacêuticos mais próximos da população - Romano, Cinthia; Simão, Elaine; Joaquim, Larissa Ferres; Ponti, Isabelle V.; de Paula, Talita G.; Bernardelli, Janaina; Prison, Karina; Guimarães, Ana Renata B.; Mendes, Fabia A.; Monteiro, Carla L.; et al. (Experiências Exitosas de Farmacêuticos no SUS, 2015)
Serviços farmacêuticos mais próximos da população